1998
DOI: 10.1200/jco.1998.16.8.2672
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preoperative chemotherapy on the outcome of women with operable breast cancer.

Abstract: Preoperative chemotherapy is as effective as postoperative chemotherapy, permits more lumpectomies, is appropriate for the treatment of certain patients with stages I and II disease, and can be used to study breast cancer biology. Tumor response to preoperative chemotherapy correlates with outcome and could be a surrogate for evaluating the effect of chemotherapy on micrometastases; however, knowledge of such a response provided little prognostic information beyond that which resulted from postoperative therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

45
1,246
6
76

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,981 publications
(1,373 citation statements)
references
References 14 publications
45
1,246
6
76
Order By: Relevance
“…Evidence suggests that a pCR correlates with better survival, and it may serve as a surrogate marker of clinical benefit. 24,25 Factors like hormone receptor status play a part in attaining a pCR with neoadjuvant chemotherapy. Patients with ER-negative tumors are more likely to achieve a pCR after neoadjuvant chemotherapy than those with ER-positive tumors.…”
Section: Evaluating the Efficacy Of Neoadjuvant Therapymentioning
confidence: 99%
“…Evidence suggests that a pCR correlates with better survival, and it may serve as a surrogate marker of clinical benefit. 24,25 Factors like hormone receptor status play a part in attaining a pCR with neoadjuvant chemotherapy. Patients with ER-negative tumors are more likely to achieve a pCR after neoadjuvant chemotherapy than those with ER-positive tumors.…”
Section: Evaluating the Efficacy Of Neoadjuvant Therapymentioning
confidence: 99%
“…The neoadjuvant and adjuvant chemotherapy comprise different drug combinations, according to the individual patient situation. Although the neoadjuvant therapy has not demonstrated convincing evidence regarding survival benefit (16), it has certain advantages, such as downstaging of an inoperable cancer to an operable one, increasing the possibility of breast-conserving surgery and potentially reducing the risk of metastatic disease (1,7). Although the type of therapy is important for survival and quality of life after treatment, the prognosis prior to treatment initiation and the monitoring of the outcome following treatment are equally important.…”
Section: Introductionmentioning
confidence: 99%
“…Results from the NSABP B-18 study confirmed that neoadjuvant and adjuvant chemotherapy are equally effective on locoregional disease in women with operable breast cancer. Moreover, this study demonstrated that clinical and pathological response to neoadjuvant chemotherapy is predictive of patient outcome (Fisher et al, 1997(Fisher et al, , 1998. However, the failure of a number of tumours to respond to treatment and the appearance of resistant tumour cell populations upon relapse of an originally responsive malignancy are still major impediments to successful chemotherapy.…”
mentioning
confidence: 96%